Molecular bloodmeal analyses reveal that Trypanosoma cruzi‐infected, native triatomine bugs often feed on humans in houses in central Brazil. Issue 4 (12th July 2018) - Minuzzi‐Souza, T. T. C.; Silva, L. R.; Hagström, L.; Hecht, M.; Nitz, N.; Gurgel‐Gonçalves, R.
Abstract: The identification of bloodmeal sources in triatomine bugs (Hemiptera: Reduviidae) is important in understanding vector–host associations and in measuring the risk for Chagas' disease transmission. The bloodmeal sources of triatomines infected with Trypanosoma cruzi (Trypanosomatida: Trypanosomatidae) caught in houses in central Brazil (Goiás State and the Federal District) were investigated during 2012–2014. Mitochondrial cytochrome b amplicons were used to identify bloodmeals through high‐resolution melting and DNA sequencing. Most bugs were found to have fed on either humans (45.7%) or chickens (43.1%). Human blood was detected in Triatoma sordida ( n = 22/50 bugs), Triatoma pseudomaculata ( n = 7/11 bugs), Panstrongylus megistus ( n = 10/24 bugs), Panstrongylus geniculatus ( n = 1/3 bugs) and Rhodnius neglectus ( n = 18/28 bugs) (all: Hemiptera: Reduviidae). Sequencing identified Necromys (Rodentia: Cricetidae) mouse blood in P. geniculatus and Tropidurus (Squamata: Tropiduridae) lizard blood in T. pseudomaculata and T. sordida . These findings reveal new vector–host associations. The present results suggest frequent contact between humans and T. cruzi ‐infected triatomines in central Brazil and indicate that Chagas' disease transmission by native vectors is an ongoing threat.